THE IMPACT OF LANGUAGE IN SOCIETY AND FUTURE - Nazarova Dilnoza,; Abdusamadov Zafar, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article discusses the effects of language on human culture, society, and the future. We know that language is an integral part of the human way of life, so it does not remain unaffected by other important concepts in society. In this article, I want to talk about the relationship and behaviour of language in this regard.